Analysis of Energy Consumption and Indoor Temperature Distributions in Educational Facility Based on CFD-BES Model. (May 2017) - Hong, Taehoon; Lee, Myeonghwi; Kim, Jimin
Abstract: To facilitate an increase in comfortable and healthy indoor environments, a lot of people have researched and conducted studies related to this field. However, it has proven difficult to find optimal indoor conditions because each of the elements that make up the thermal environment has different properties. Natural ventilation is an important factor in meeting and creating the thermal environment as well as improved indoor air quality. Moreover, the continuation of efforts to reduce energy consumption in buildings is also required from the design stage due to the depletion of energy resource and global warming. Therefore, this study aims to provide a material of natural ventilation for educational facilities by calculating the energy consumption of a classroom in accordance with indoor temperature distributions in summer. A target educational facility with classrooms was selected in Seoul, Republic of Korea. This study assumed that the classroom windows were fully opened and were then analyzed for indoor temperature distributions and energy consumption according to natural ventilation. In addition, the simulation was conducted based on the actual daily schedule in the school. The results were achieved by utilizing the Computer fluid dynamics simulation and Building energy simulation. This paper will be the basis of research related to occupant behavior and patterns indoors.